Current understanding of phytochemicals from Chinese herbal medicines for ferroptosis-mediated cancer prevention and treatment - Yu Hu; Wenjuan Zhai; Haipeng Chen; Leyan Li; Wenhui Gao; Yijie Wei; Jinjun Wu (Elsevier, 2022)
Ferroptosis, which has attracted much attention, is a new form of regulated cell death that is closely associated with the progression of various diseases. Ferroptosis is dependent upon intracellular iron and reactive oxygen species and is morphologically, biochemically, and genetically distinct from other nonapoptotic forms of cell death. Cumulative evidence shows that ferroptosis plays a pivotal role in the development and progression of tumorigenesis. Ferroptosis induction has become a potential effective strategy in cancer prevention and treatment in the clinic. Thus, it is worth identifying the active chemical compounds that induce ferroptosis for cancer suppression. Chinese herbal medicines (CHMs), which contain a host of bioactive phytochemicals that could target many signaling pathways, have been increasingly used worldwide due to their effects against various diseases. Compelling evidence has demonstrated that many phytochemicals from CHMs exert potent anticarcinogenic effects and have been widely used for the clinical prevention and treatment of a variety of cancers. Furthermore, growing evidence suggests that phytochemicals could exhibit potent inhibitory effects against different cancers by inducing ferroptosis through the regulation of a large number of ferroptosis-related signaling pathways and targets. Herein, we summarized the current understanding of phytochemicals from CHMs in ferroptosis-mediated cancer prevention and treatment and the molecular mechanisms. We also concluded with potential applications of emerging ferroptosis-related strategies against cancer. This study may expand our current knowledge about the mechanisms of phytochemicals from CHMs as anticancer agents, which could be used clinically to enhance the effect of future ferroptosis-inducing CHM therapies against cancers.